2021
DOI: 10.5194/bg-18-993-2021
|View full text |Cite
|
Sign up to set email alerts
|

The composition of endolithic communities in gypcrete is determined by the specific microhabitat architecture

Abstract: Abstract. Endolithic microhabitats have been described as the last refuge for life in arid and hyper-arid deserts where life has to deal with harsh environmental conditions. A number of rock substrates from the hyper-arid Atacama Desert, colonized by endolithic microbial communities such as halite, gypsum crusts, gypcrete, calcite, granite and ignimbrite, have been characterized and compared using different approaches. In this work, three different endolithic microhabitats are described, each one with a partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
12
1
Order By: Relevance
“…Although Chroococcidiopsis is the dominant cyanobacterium in endolithic habitats in hot deserts, such as the Atacama (Dong et al ., 2007; Crits‐Christoph et al ., 2016; Meslier et al ., 2018; Ertekin et al ., 2020; Qu et al ., 2020; Casero et al ., 2021), Negev (Israel) and Namib (southern Africa) Deserts (Qu et al ., 2020), other coccoid taxa have also been found in endolithic assemblages from the Atacama Desert, such as Gloeocapsa (Crits‐Christoph et al ., 2016; Ertekin et al ., 2020. ; Casero et al ., 2021) and Halothece (Ertekin et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Chroococcidiopsis is the dominant cyanobacterium in endolithic habitats in hot deserts, such as the Atacama (Dong et al ., 2007; Crits‐Christoph et al ., 2016; Meslier et al ., 2018; Ertekin et al ., 2020; Qu et al ., 2020; Casero et al ., 2021), Negev (Israel) and Namib (southern Africa) Deserts (Qu et al ., 2020), other coccoid taxa have also been found in endolithic assemblages from the Atacama Desert, such as Gloeocapsa (Crits‐Christoph et al ., 2016; Ertekin et al ., 2020. ; Casero et al ., 2021) and Halothece (Ertekin et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent culture‐dependent and culture‐independent studies, also in the Atacama Desert, have shown the occurrence of Synechococcus , Gloeocapsopsis (Casero et al ., 2021), Aliterella , and Pleurocapsa minor (Jung et al ., 2019). In addition, the filamentous, non‐heterocystous Trichocoleus sociatus and the heterocystous S. hyalinum (Jung et al ., 2019) and Calothrix and Fischerella (Casero et al ., 2021) were also found. However, clear differences were found in polar deserts with increased abundances of filamentous, non‐heterocystous cyanobacteria, such as Phormidium (Qu et al ., 2020; Khomutovska et al ., 2021a, 2021b), Leptolyngbya , and Nodosilinea (Rego et al ., 2019; Khomutovska et al ., 2021a, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endolithic algae inhabit the inner surfaces or fissures of stones and rocks and comprise a very specific community, which after the pioneer works by Imre Friedmann and his colleagues (e.g., [276][277][278][279] is considered extremophilic [7,280,281]. Nevertheless, little is known about the global biodiversity of algal endoliths, but despite some fine-scale partitioning depending on the rock types and local climate conditions, the similarity in species composition allows to generalize that cyanoprokaryotes, and the polyextremophilic BMAA producing [126] genus Chroococcidiopsis in particular, often dominates [4, 13,[280][281][282][283][284][285][286][287]. Among all recorded endolithic algae, occur other genera, from which toxigenic species have been found in different, mainly aquatic habitats: Anabaena, Aphanocapsa, Lyngbya, Phormidium and Plectonema (e.g., [276][277][278][279]284,[287][288][289][290][291][292][293][294][295]) (Table 1).…”
Section: Aeroterrestrial Endolithic Algaementioning
confidence: 99%
“…The unicellular coccal cyanoprokaryote Synechocystis sp PCC68034 is able to accumulate large concentrations of Mn 2+ [13]. The IR-resistance in the coccal cyanoprokaryote Chroococcidiopsis from desert and hypersaline environments possibly reflects its ability a to survive prolonged desiccation due to its thick protective mucilaginous (extracellular polysaccharide) envelopes and intracellular trehalose accumulation, as well as through efficient repair of the DNA damage that accumulates during dehydration [283,285,286]. There are no targeted toxin investigations on these radioresistant strains, but both genera have been reported as cyanotoxin producers [73,126] (Table 1).…”
Section: Toxigenic Radioresistant Algaementioning
confidence: 99%